Composite current collector, battery cell and electric equipment

By using a composite liquid collector of an intermediate layer and a conductive layer with a large high-temperature expansion coefficient in lithium batteries, the thermal runaway problem of lithium batteries is solved, and the effect of electrical connection is cut off at low impedance and high temperature is achieved, which improves battery safety performance.

CN222355153UActive Publication Date: 2025-01-14BYD CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420957850.X
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2025-01-14
Estimated Expiration
2034-04-29

AI Technical Summary

Technical Problem

In abnormal situations, traditional lithium batteries have direct contact with the positive electrode aluminum foil and the fully charged graphite negative electrode, which leads to thermal runaway, affecting battery performance.

Method used

A composite fluid collector is used, including an intermediate layer and a conductive layer, which has a high temperature expansion coefficient and expands at high temperature to pull a distance between conductive particles in the conductive layer, increase resistance, cut off electrical connections, and prevent thermal runaway.

Benefits of technology

The conductive particles are in good contact with each other at the normal temperature of the battery and have a small impedance; when thermal runaway is about to occur, the expansion of the intermediate layer causes the impedance of the conductive layer to increase sharply, cutting off the electrical connection and preventing the battery from getting out of control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222355153U_ABST
    Figure CN222355153U_ABST
Patent Text Reader

Abstract

The utility model provides a composite current collector which comprises a middle layer and conductive layers arranged on the two sides of the middle layer in the thickness direction, the high-temperature expansion coefficient of the middle layer is 10 <-5 > / DEG C to 10 <-3 > / DEG C, and the conductive layers comprise conductive particles. The high-temperature expansion coefficient of the middle layer is large, the conductive layers containing the conductive particles are arranged on the two sides of the middle layer, and under the normal-temperature use environment (-30 DEG C to 65 DEG C) of the battery, the contact between the conductive particles is good, and the impedance is small; when the battery is about to be subjected to thermal runaway or internal short circuit, the middle layer can expand, so that the distance between the conductive particles in the conductive layers on the two sides is increased, and the impedance is sharply increased (the difference is 7-8 orders of magnitude), so that the electric connection is cut off, and the thermal runaway of the battery is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of batteries, and specifically relates to a composite current collector, a battery core and electrical equipment. Background Art

[0002] The safety performance of lithium batteries has always received widespread attention. In general, batteries are mainly composed of positive electrodes, negative electrodes, separators, electrolytes and shells. There is a potential difference between the positive and negative electrodes to provide the battery voltage; the separator is between the positive and negative electrodes and acts as an insulator; the electrolyte can provide lithium ions to shuttle between the positive and negative electrodes to ensure the charging and discharging functions. The negative electrode current collector of traditional lithium-ion batteries is copper foil, and the positive electrode current collector is aluminum foil. Under abnormal circumstances, the direct contact between the positive aluminum foil current collector and the fully charged graphite negative electrode is the most direct factor for the heating and fire of lithium batteries. At this time, the battery will experience thermal runaway, affecting battery performance. Utility Model Content

[0003] In view of the problems existing in the prior art, the present application provides a composite current collector, a battery cell and an electrical device.

[0004] In order to solve the above problems, this application provides the following technical solutions:

[0005] In a first aspect, the present application provides a composite current collector, comprising an intermediate layer and conductive layers arranged on both sides of the intermediate layer in a thickness direction, wherein the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / °C, the conductive layer includes conductive particles.

[0006] In some embodiments, the high temperature expansion coefficient of the intermediate layer is 0.5×10 -5 / ℃~10 -4 / ℃.

[0007] In some embodiments, in a direction perpendicular to the thickness of the intermediate layer, the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / ℃.

[0008] In some embodiments, the middle layer includes a high molecular polymer, and the high molecular polymer includes one of polyethylene, polypropylene, and polyethylene terephthalate.

[0009] In some embodiments, the conductive particles include one of nickel-chromium alloy particles, nickel-copper alloy particles, nickel-molybdenum alloy particles, nickel-tungsten alloy particles, nickel-chromium-molybdenum alloy particles, nickel-chromium-molybdenum-copper alloy particles, copper particles, gold particles, silver particles, aluminum particles, copper oxide particles, iron oxide particles, and zinc oxide particles.

[0010] In some embodiments, the conductive particles are further coated with one of carbon nanotubes, graphene, carbon black, and conductive graphite, and / or the conductive layer further includes one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fiber, and graphene.

[0011] In some embodiments, the thickness of the intermediate layer is 2um to 10um; the thickness of the conductive layer is 2um to 5um.

[0012] In some embodiments, the D90 particle size of the conductive particles is 50 nm to 500 nm.

[0013] In one embodiment, the D90 particle size of the conductive particles is 100 nm to 500 nm.

[0014] In some embodiments, the intermediate layer further includes pores, and an average pore size of the pores is smaller than a D90 particle size of the conductive particles.

[0015] In a second aspect, the present application provides a battery cell comprising the composite current collector described in the first aspect.

[0016] In some embodiments, the battery cell includes a positive electrode active material layer and a negative electrode active material layer, and the positive electrode active material layer and the negative electrode active material layer are respectively disposed on both sides of the composite current collector in a thickness direction.

[0017] In a third aspect, the present application provides an electrical device comprising the battery cell described in the second aspect.

[0018] The composite current collector provided by the present application has the following technical effects: the high-temperature expansion coefficient of the intermediate layer of the present application is relatively large, and conductive layers containing conductive particles are arranged on both sides of the intermediate layer. Under the normal temperature use environment of the battery (-30°C ~ 65°C), the conductive particles have good contact and low impedance; when the battery is about to have thermal runaway or internal short circuit, the intermediate layer will expand, causing the distance between the conductive particles in the conductive layers on both sides to be increased, and the impedance will increase sharply (the difference is 7 to 8 orders of magnitude), thereby cutting off the electrical connection and preventing the occurrence of thermal runaway of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the utility model or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the utility model. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0020] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0022] Figure 1 It is a schematic diagram of the composite current collector structure in some embodiments of the utility model;

[0023] Figure 2 It is a schematic diagram of the battery cell structure in some embodiments of the utility model.

[0024] Explanation of reference numerals: A: intermediate layer; B: conductive layer; C: positive electrode active material layer; D: negative electrode active material layer; O: conductive particles. DETAILED DESCRIPTION

[0025] In order to make the technical problems, technical solutions and beneficial effects solved by the utility model more clear, the utility model is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described here are only used to explain the utility model and are not used to limit the utility model.

[0026] In a first aspect, the utility model provides a composite current collector, comprising an intermediate layer and conductive layers arranged on both sides of the intermediate layer in a thickness direction, wherein the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / ℃, the conductive layer includes conductive particles.

[0027] Specifically, in this application, the high temperature expansion coefficient refers to the change in length or volume value caused by a unit temperature change of an object at a temperature of 65°C-135°C under standard atmospheric pressure, and the unit is usually 1 / °C; the change in length value caused by a unit temperature change corresponds to the linear expansion coefficient, the change in volume value caused by a unit temperature change corresponds to the volume expansion coefficient, and the linear expansion coefficient Volume expansion coefficient Where L and V are the original length and volume of the sample, respectively; dl and dv are the relative elongation and volume changes of the sample when the temperature rises from t1 (℃) to t2 (℃).

[0028] In this application, the high temperature expansion coefficient of the middle layer A is 10 -5 / ℃~10 -3 / ℃ means that at a temperature of 65℃-135℃ and under standard atmospheric pressure, the change in the length and / or volume of the middle layer A is 10 -5 / ℃~10 -3 / ℃. The larger the high temperature expansion coefficient of an object, the greater the change in length or volume caused by a unit temperature change. The high temperature expansion coefficient of the middle layer A can be, but is not limited to, 10 -5 / ℃、10 -4 / ℃、10 -3 / ℃.

[0029] Specifically, the composite current collector provided in the present application has a three-layer structure of conductive layer B-intermediate layer A-conductive layer B. The conductive layer contains conductive particles O. The conductive particles O refer to conductive substances in the shape of particles. The conductive layer contains conductive particles to improve the conductive properties of the composite current collector.

[0030] The intermediate layer A provided in the present application can, firstly, provide a load matrix for the conductive layer; secondly, it expands when the temperature of the current collector is higher than 65°C, thereby increasing the distance between the conductive particles O in the conductive layer B on both sides of the intermediate layer, increasing the resistance of the conductive layer, cutting off the current, and avoiding thermal runaway of the battery.

[0031] The composite current collector provided by the present application has the following effects: the high-temperature expansion coefficient of the intermediate layer A of the present application is relatively large, and a conductive layer B containing conductive particles O is arranged on both sides of the intermediate layer. In the normal temperature use environment of the battery (-30°C ~ 65°C), the conductive particles O have good contact with each other and low impedance; when the battery is about to have thermal runaway or internal short circuit, the intermediate layer A will expand, causing the distance between the conductive particles O in the conductive layers B on both sides to be enlarged, and the impedance will increase sharply (the difference is 7 to 8 orders of magnitude), thereby cutting off the electrical connection and preventing the occurrence of thermal runaway of the battery.

[0032] In some preferred embodiments, the high temperature expansion coefficient of the intermediate layer is 0.5×10 -5 / ℃~10 -4 / ℃.

[0033] The high temperature expansion coefficient of the middle layer is 0.5×10 -5 / ℃~10 -4 / ℃, the safety performance of the battery can be better improved and thermal runaway of the battery can be avoided.

[0034] In some embodiments, in a direction perpendicular to the thickness of the intermediate layer, the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / ℃.

[0035] Specifically, the thickness direction of the intermediate layer A is the thickness direction of the composite current collector. In the thickness direction perpendicular to the intermediate layer A, the intermediate layer A will expand at high temperature, and its high temperature expansion coefficient satisfies 10 -5 / ℃~10 -3 / ℃, expanding in this direction can more effectively increase the distance between the conductive particles O in the conductive layer B, causing the impedance of the middle layer A to increase sharply, thereby better cutting off the electrical connection and preventing thermal runaway of the battery.

[0036] In some embodiments, the middle layer includes a high molecular polymer, and the high molecular polymer includes one of polyethylene, polypropylene, and polyethylene terephthalate.

[0037] Specifically, the middle layer A includes a high molecular polymer, and the high molecular polymer includes one of polyethylene, polypropylene, and polyethylene terephthalate. The high temperature expansion coefficients of polyethylene, polypropylene, and polyethylene terephthalate are 1.5×10 -4 / ℃、1.2×10 -4 / ℃、8×10 -5 / ℃, the middle layer A includes polyethylene, polypropylene, polyethylene terephthalate, so that the high temperature expansion coefficient of the middle layer is 10 -5 / ℃~10 -3 / ℃ range, it can better meet the expansion effect of the intermediate layer A of the composite current collector at high temperature, cut off the electrical connection, and prevent the occurrence of thermal runaway of the battery. When the intermediate layer A includes a high molecular polymer, its expansion process is reversible. When the temperature of the battery core returns to normal, the high molecular polymer shrinks, the distance between the conductive particles O is reduced, and the impedance is reduced.

[0038] In some embodiments, the conductive particles include one of nickel-chromium alloy particles, nickel-copper alloy particles, nickel-molybdenum alloy particles, nickel-tungsten alloy particles, nickel-chromium-molybdenum alloy particles, nickel-chromium-molybdenum-copper alloy particles, copper particles, gold particles, silver particles, aluminum particles, copper oxide particles, iron oxide particles, and zinc oxide particles.

[0039] Specifically, the conductive particles O include alloy particles such as nickel-chromium alloy particles, nickel-copper alloy particles, nickel-molybdenum alloy particles, nickel-tungsten alloy particles, nickel-chromium-molybdenum alloy particles, nickel-chromium-molybdenum-copper alloy particles, copper particles, gold particles, silver particles, aluminum particles and other pure metal particles, copper oxide particles, iron oxide particles, zinc oxide particles and other metal oxide particles, among which the alloy particles have good high temperature resistance, the pure metal particles have excellent electrical conductivity, and the metal oxide particles have lithium affinity. By controlling the distance between the conductive particles O to control the impedance of the conductive layer B, the requirements of the composite current collector can be better met and the safety performance of the battery can be improved.

[0040] In some embodiments, the conductive particles are coated with one of carbon nanotubes, graphene, carbon black, and conductive graphite, and / or the conductive layer further includes one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fiber, and graphene.

[0041] Specifically, coating the conductive particles O with one of carbon nanotubes, graphene, carbon black, and conductive graphite, and / or adding one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fibers, and graphene to the conductive layer can increase the conductivity between the conductive particles O and the overall conductivity of the conductive layer B, which is beneficial to improving the cycle performance of the battery.

[0042] Specifically, one of carbon nanotubes, graphene, carbon black, and conductive graphite is coated on the outside of the conductive particles O. Coating the conductive particles O with one of carbon nanotubes, graphene, carbon black, and conductive graphite can enhance the conductivity between the conductive particles O and the conductive layer B, and / or, adding carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fiber, and graphene to the conductive layer B can also improve the conductivity of the composite current collector. Different technical solutions can be applied according to different battery requirements.

[0043] In some embodiments, the thickness of the intermediate layer is 2um to 10um; the thickness of the conductive layer is 2um to 5um.

[0044] Specifically, the thickness of the intermediate layer A can be, but is not limited to, 2um, 3um, 4um, 5um, 6um, 7um, 8um, 9um, and 10um. The thinner the thickness of the intermediate layer A is, the better the overall energy density of the battery is, and the better the overall performance of the battery is; the thicker the thickness of the intermediate layer A is, the better the mechanical strength of the composite current collector is, and the conductive layers B on both sides can be better supported. Therefore, the thickness of the intermediate layer A is within this range, which can ensure both the overall energy density of the battery and the mechanical strength of the composite current collector.

[0045] Specifically, the thickness of the conductive layer B is 2um to 5um, which means that the thickness of the conductive layer on one side of the intermediate layer A is 2um to 5um. The thickness of the conductive layer B can be, but is not limited to, 2um, 3um, 4um, and 5um. The thinner the thickness of the conductive layer B, the better the energy density of the battery cell, the better the electrochemical performance of the battery, and the lower the cost; the thicker the thickness of the conductive layer B, the smaller the impedance of the conductive layer B, and the better the conductive performance. Therefore, when the thickness of the conductive layer B is within this range, it can not only ensure the energy density of the battery and save costs, but also increase the conductive performance of the conductive layer and reduce impedance.

[0046] In some embodiments, the D90 particle size of the conductive particles O is 50 nm to 500 nm.

[0047] Specifically, the D90 particle size of the conductive particles O refers to the particle size corresponding to when the number distribution percentage of the conductive particles reaches 90%. The D90 particle size of the conductive particles O can be, but is not limited to, 50nm, 100nm, 150nm, 200nm, 300nm, 400nm, and 500nm. The smaller the D90 particle size of the conductive particles O, the better the conductive performance of the conductive layer B, and the smaller the overall impedance of the composite current collector; the larger the D90 particle size of the conductive particles O, the more feasible the process of the conductive particles O is, and the more convenient it is for industrial production. The particle size of the conductive particles O within this range can not only ensure the conductive performance of the conductive layer B and reduce the impedance, but also be convenient to implement in the process, which is conducive to industrial production.

[0048] In some embodiments, the D90 particle size of the conductive particles is 100 nm to 500 nm.

[0049] Specifically, the D90 particle size of the conductive particles O is in the range of 100 nm to 500 nm, which can better increase the conductivity of the composite current collector and facilitate industrial production.

[0050] In some embodiments, the intermediate layer further comprises pores, and an average pore size of the pores is smaller than a D90 particle size of the conductive particles.

[0051] Specifically, the intermediate layer A includes pores, and the test method for the average pore size of the pores can refer to GB / T38949-2020. The pores in the intermediate layer A can increase the permeability of the composite current collector, which is beneficial to reducing the overall impedance of the composite current collector and improving the cycle life and energy density of the battery. The average pore size of the pores is smaller than the D90 particle size of the conductive particles O, which can block the conductive particles O outside the intermediate layer A without blocking the pores of the intermediate layer A, which is beneficial to enhancing the permeability of the composite current collector, reducing the impedance of the composite current collector, and improving the overall performance of the battery.

[0052] In a second aspect, the present application provides a battery cell comprising the composite current collector described in the first aspect.

[0053] In some embodiments, the battery cell includes a positive electrode active material layer and a negative electrode active material layer, and the positive electrode active material layer and the negative electrode active material layer are respectively disposed on both sides of the composite current collector in the thickness direction.

[0054] Specifically, the battery cell includes a positive electrode active material layer C and a negative electrode active material layer D. The positive electrode active material layer C and the negative electrode active material layer D are respectively arranged on both sides of the composite current collector in the thickness direction, which means that the positive electrode active material layer C is arranged on one side of the composite current collector, and the negative electrode active material layer D is arranged on the other side. No separator is required, and the positive electrode active material layer C, the negative electrode active material layer D and the composite current collector are directly compounded together to form a minimum active unit of the battery cell, which reduces the use of separators and current collectors, and is beneficial to improving the energy density of the battery.

[0055] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.

[0056] Specifically, the positive electrode active material layer C and the negative electrode active material layer D are arranged on both sides of the composite current collector in the thickness direction, and the positive electrode active material layer C includes a positive electrode active material, a conductive agent, and a binder; the negative electrode active material layer D includes a negative electrode active material, a conductive agent, and a binder. The positive electrode active material layer C and the negative electrode active material layer D are both conventionally used in the art and belong to the prior art, and will not be described in detail here.

[0057] In a third aspect, the present application provides an electrical device comprising the battery cell described above.

[0058] Electrical equipment includes, but is not limited to, mobile phones, laptops, tablets, cameras, televisions, radios, wearable devices (such as smart watches, smart bracelets, head-mounted stereo headphones, Bluetooth headsets), backup power supplies, new energy vehicles, power tools, large household batteries, etc.

[0059] The present invention is further described in detail below through embodiments.

[0060] Example 1

[0061] This embodiment is used to illustrate the composite current collector, battery core and electrical equipment disclosed in the utility model, and includes the following steps:

[0062] (1) Preparation of composite current collector:

[0063] Conductive particles O (specifically nickel-chromium alloy particles) are sprayed on the middle layer A (specifically polyethylene), and a composite current collector is obtained by hot pressing; wherein the thickness of the middle layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0064] (2) Preparation of positive electrode:

[0065] Lithium iron phosphate, conductive agent Super P (superconducting carbon), and binder PVDF (polyvinylidene fluoride) are mixed uniformly in a mass ratio of 95:2.5:2.5 to form a slurry with a certain viscosity, which is coated on one side of the composite current collector prepared in (1) and dried at 85°C.

[0066] (3) Preparation of negative electrode:

[0067] Graphite, conductive agent SuperP (superconducting carbon), thickener CMC (sodium carboxymethyl cellulose), and binder SBR (styrene-butadiene rubber) are mixed uniformly in a mass ratio of 96:2:1:1 to form a slurry with a certain viscosity, which is then coated on the other side of the composite current collector obtained in (2), dried at 85°C, rolled, and cut.

[0068] (4) Preparation of lithium-ion batteries:

[0069] The assembled battery cell is subjected to subsequent processes such as liquid injection, formation, and capacity separation to obtain a lithium-ion battery.

[0070] Example 2

[0071] The difference between Example 2 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0072] (1) Preparation of composite current collector:

[0073] Conductive particles O (specifically, carbon black-coated nickel-chromium alloy particles) are sprayed on the intermediate layer A (specifically, polyethylene), and a composite current collector is obtained by hot pressing; wherein the thickness of the intermediate layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0074] Example 3

[0075] The difference between Example 3 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0076] (1) Preparation of composite current collector:

[0077] Conductive particles O (specifically, carbon black-coated nickel-chromium alloy particles) are sprayed on the intermediate layer A (specifically, polypropylene), and a composite current collector is obtained by hot pressing; wherein the thickness of the intermediate layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0078] Example 4

[0079] The difference between Example 4 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0080] (1) Preparation of composite current collector:

[0081] Conductive particles O (specifically, carbon black-coated nickel-chromium alloy particles) are sprayed on the intermediate layer A (specifically, polyethylene terephthalate), and a composite current collector is obtained by hot pressing; wherein the thickness of the intermediate layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0082] Example 5

[0083] The difference between Example 5 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0084] (1) Preparation of composite current collector:

[0085] Conductive particles O (specifically, nickel-copper alloy particles coated with carbon black) are sprayed on the intermediate layer A (specifically, polyethylene), and a composite current collector is obtained by hot pressing; wherein the thickness of the intermediate layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0086] Example 6

[0087] The difference between Example 6 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0088] (1) Preparation of composite current collector:

[0089] Conductive particles O (specifically, nickel-molybdenum alloy particles coated with carbon black) are sprayed on the intermediate layer A (specifically, polyethylene), and a composite current collector is obtained by hot pressing; wherein the thickness of the intermediate layer A is 5um, the thickness of the single-sided conductive layer B is 3um, and the D90 particle size of the conductive particles O is 100nm.

[0090] Comparative Example 1

[0091] The difference between Comparative Example 1 and Example 1 is that the preparation of the composite current collector is different, and the rest is the same as Example 1.

[0092] (1) Preparation of positive electrode:

[0093] Lithium iron phosphate, conductive agent Super P (superconducting carbon), and binder PVDF (polyvinylidene fluoride) are mixed evenly in a mass ratio of 95:2.5:2.5 to form a slurry with a certain viscosity, coated on aluminum foil, dried at 85°C, rolled, and cut to obtain the required positive electrode.

[0094] (2) Preparation of negative electrode:

[0095] Graphite, conductive agent SuperP (superconducting carbon), thickener CMC (sodium carboxymethyl cellulose), and binder SBR (styrene-butadiene rubber) are mixed evenly in a mass ratio of 96:2:1:1 to form a slurry with a certain viscosity, coated on copper foil, dried at 85°C, rolled, and cut to obtain the desired negative electrode.

[0096] (3) Preparation of lithium-ion batteries:

[0097] The positive electrode and negative electrode prepared in (1) and (2) are assembled with a separator into a battery cell, and a lithium-ion battery is obtained through subsequent processes such as liquid injection, formation, and capacity separation.

[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite current collector, characterized in that: It includes an intermediate layer and conductive layers arranged on both sides of the intermediate layer in the thickness direction, and the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / °C, the conductive layer includes conductive particles.

2. The composite current collector according to claim 1, wherein the high temperature expansion coefficient of the intermediate layer is 0.5×10 -5 / ℃~10 -4 / ℃.

3. The composite current collector according to claim 1, characterized in that: In the direction perpendicular to the thickness of the intermediate layer, the high temperature expansion coefficient of the intermediate layer is 10 -5 / ℃~10 -3 / ℃.

4. The composite current collector according to claim 1, characterized in that: The middle layer includes a high molecular polymer, and the high molecular polymer includes one of polyethylene, polypropylene, and polyethylene terephthalate.

5. The composite current collector according to claim 1, characterized in that: The conductive particles include one of nickel-chromium alloy particles, nickel-copper alloy particles, nickel-molybdenum alloy particles, nickel-tungsten alloy particles, nickel-chromium-molybdenum alloy particles, nickel-chromium-molybdenum-copper alloy particles, copper particles, gold particles, silver particles, aluminum particles, copper oxide particles, iron oxide particles, and zinc oxide particles.

6. The composite current collector according to claim 1, characterized in that: The conductive particles are coated with one of carbon nanotubes, graphene, carbon black, and conductive graphite, and / or the conductive layer further comprises one of carbon black, acetylene black, Ketjen black, conductive graphite, carbon nanotubes, carbon fiber, and graphene.

7. The composite current collector according to claim 1, characterized in that: The thickness of the intermediate layer is 2um to 10um; the thickness of the conductive layer is 2um to 5um.

8. The composite current collector according to claim 1, characterized in that: The D90 particle size of the conductive particles is 50nm to 500nm.

9. The composite current collector according to claim 8, characterized in that: The D90 particle size of the conductive particles is 100 nm to 500 nm.

10. The composite current collector according to claim 8 or 9, characterized in that: The intermediate layer further includes pores, and an average pore size of the pores is smaller than a D90 particle size of the conductive particles.

11. A battery cell, characterized in that: The composite current collector comprises the composite current collector according to any one of claims 1 to 10.

12. The battery cell according to claim 11, characterized in that: The battery core comprises a positive electrode active material layer and a negative electrode active material layer, and the positive electrode active material layer and the negative electrode active material layer are respectively arranged on both sides of the composite current collector in a thickness direction.

13. An electrical equipment, characterized in that: Comprising the battery cell according to claim 11 or 12.